Community Service Activities On Providing Additional Food For The Elderly At The Village Health Post, Sukaraya Village, Pancur Batu District, Deli Serdang Regency, 2025 - Lidia Silaban; Roikestina Silaban; Faija Sihombing (CV. AFDIFAL MAJU BERKAH, 2025)
The elderly are a vulnerable group at high risk of experiencing nutritional problems due to various factors such as decreased appetite, digestive disorders, and economic and social limitations. Poor nutritional status in the elderly can increase susceptibility to disease and reduce quality of life. This community service activity aims to improve the nutritional status and awareness of the elderly about the importance of consuming nutritious food through the provision of supplementary food (PMT). The activity was carried out at the Village Health Post (Poskesdes) in Sukaraya Village, Pancur Batu District, Deli Serdang Regency in 2025. The methods used included nutrition counseling, simple health checks, demonstrations of making supplementary food from local ingredients, and distribution of PMT consisting of mung bean porridge, biscuits, milk, and fruit. A total of 50 elderly people actively participated in this activity. Evaluation results showed an increase in participants' knowledge about the importance of balanced nutrition and motivation to improve their daily diet. The elderly also said they felt happy and helped by the PMT that could support their daily nutritional needs. This activity not only focused on providing supplementary food but also strengthened education so that the elderly could implement a healthy diet independently. It is hoped that community service activities like this can continue to be carried out sustainably to support promotive and preventive efforts in improving the health status of the elderly and realizing healthy, independent, and productive elderly people